Agrobacterium-Mediated Transformation of Tree Fruit Crops: Methods, Progress, and Challenges - Song, Guo-qing; Prieto, Humberto; Orbovic, Vladimir (Frontiers in Plant Science, 2019)
Genetic engineering based on Agrobacterium-mediated transformation has become a desirable tool to manipulate single or multiple genes of existing genotypes of woody fruit crops, for which conventional breeding is a difficult and lengthy process due to heterozygosity, sexual incompatibility, juvenility, or a lack of natural sources. To date, successful transformation has been reported for many fruit crops. We review the major progress in genetic transformation of these fruit crops made in the past five years, emphasizing reproducible transformation protocols as well as the strategies that have been tested in fruit crops. Transgenesis was the major strategy used mainly for fruit quality improvement, biotic and abiotic tolerance, and functional gene analysis in fruit crops. Cisgenesis and transgrafting showed a potential to minimize the public’s concern about the use of transgenesis. More recently, genome editing technologies showed promise in providing powerful tools for gene(s) manipulation. We believe that effective transient transformation and efficient regeneration are the key for utilizing genome editing technologies for fruit crops.